Budaya Belajar pada Lembaga Formal Pendidikan Islam: Studi Kasus di MTs Roudlotul Khuffadz - Ulil Albab Al Jawad; Muhammad Sidek; Amsia Reasa; Indria Nur; Sukman Sappe; Ismail Suardi Wekke (Qalam : Jurnal Ilmu Kependidikan, 2024)
This research explores the implementation of Islamic learning culture at MTs Roudlotul Khuffadz. The aim of this research is to uncover the applied learning culture, with the goal not only to achieve material proficiency but also to shape individuals who are mature and possess a positive learning culture. The research method used is qualitative, involving observation of daily activities at MTs Roudlotul Khuffadz and interviews to map indicators of student learning culture and its contributing factors. Data analysis is conducted using the Spradley method, encompassing domain analysis, taxonomy, componential analysis, and cultural theme analysis. The results of the research indicate that the implementation of Islamic learning culture at MTs Roudlotul Khuffadz is realized through systematic planning, incorporating Islamic elements, daily routines, and the cultivation of Islamic values such as worship, good behavior, noble character, manners, and daily habits. In conclusion, MTs Roudlotul Khuffadz has successfully implemented the Islamic learning culture by engaging all stakeholders, including students, parents, and educators. Islamic leadership is key in creating a school that serves as a model for Islamic learning culture.